PEMBERDAYAAN USAHA JAJAN UPAKARA SEBAGAI SARANA UPACARA KEAGAMAAN DI JIMBARAN - Wahyuni, Luh Mei; Pratiwi, Ni Made Wirasyanti Dwi; Sukarata, Putu Gde (SELAPARANG: Jurnal Pengabdian Masyarakat Berkemajuan, 2023)
ABSTRAKBanyaknya pelaksanaan upacara dalam Agama Hindu di Bali, menyebabkan kebutuhan sarana perlengkapan upacara terus meningkat dan berkembang khususnya kebutuhan jajanan khas Bali yang digunakan dalam pelaksanaan upacara. Hal ini menjadi peluang bagi usaha jajan bali berkembang. Mitra dalam kegiatan pemberdayaan masyarakat ini adalah usaha Jajan Upakara Bali yang berlokasi di dusun Jl. Uluwatu Gang Menaga Jati No 8 Jimbaran. Jajan Upakara Bali merupakan usaha kecil yang memproduksi Jajan untuk kegiatan upacara keagamaan yang terdiri dari produk jajan uli dan jajan begina khas Bali. Karena merupakan usaha yang diturunkan dari tradisi maka terdapat beberapa kendala berupa keterbatasan alat bantu produksi, pengemasan produk, kurangnya manajemen keuangan serta keterbatasan dalam hal pemasaran. Berdasarkan permasalahan yang dihadapi, maka akan dilakukan kegiatan bertahap mulai manajemen produksi sampai pemasaran. Tujuan kegiatan ini adalah meningkatkan kinerja produksi Jajan Bali, memberikan kepastian mengenai pendapatan usaha sehingga mitra dapat dengan mudah membuat perencanaan produksi maupun pemasaran, meningkatkan pemasaran mitra sehingga usaha mitra lebih dikenal oleh masyarakat. Metode pelaksanaan terdiri dari tahap sosialisasi, peningkatan alat produksi, pengemasan yang menarik, pelatihan manajemen keuangan dan pemasaran serta evaluasi kegiatan. Kegiatan dimulai dengan sosialisasi, pemberian peralatan sebagai alat bantu produksi seperti mesin parut, kompor, wajan, mesin sealer, alas jemur jajan, alat cetak jajan, box besi penyimpanan, pemberian bantuan kemasan dan label kemasan, pelatihan pengemasan, pelatihan manajemen keuangan, pembuatan media sosial dan pelatihan penggunaan media sosialsocial. Hasil kegiatan Berdasarkan hasil evaluasi, tahap pertama didapatkan dengan adanya penambahan alat produksiberupa percmempercepatan  proses produksi  sebanyak 50% sehinggadan menghemat waktu produksi 50%, peningkatan produksi sebanyak 50%, . Dari segi pengemasan, 100% produk telah berisi label kemasan, 1 orang anggota mitra dapat membuat manajemen keuangan sederhana. Kata kunci: pemberdayaan usaha; sarana upakara; jajan bali. ABSTRACTThe partner in this community empowerment activity is the Upakara Bali Snacks business. Jajan Upakara Bali produces snacks for religious ceremonies consisting of Balinese uli and bena snack products. Because it is a business derived from tradition, there are several obstacles in the form of limited production tools, product packaging, lack of financial management and limitations in terms of marketing. Based on the problems faced, gradual activities will be carried out starting from production management to marketing. The aim of this activity is to improve the production performance of Balinese Snacks, provide certainty regarding business income so that partners can easily make production and marketing plans, improve partner marketing so that partner businesses are better known to the public. The implementation method consists of the socialization stage, improving production equipment, attractive packaging, financial and marketing management training and activity evaluation. Activities began with socialization, providing equipment as production aids such as grating machines, stoves, frying pans, sealer machines, snack drying mats, snack molding equipment, metal storage boxes, providing assistance with packaging and packaging labels, packaging training, financial management training, media making social and training in the use of social media. The results of the activity are in the form of accelerating the production process thereby saving production time by 50%, increasing production by 50%, 100% of products contain packaging labels, 1 partner member can make financial management simple.The large number of ceremonies carried out in Hinduism in Bali, causes the need for ceremonial equipment to continue to increase and develop, especially the need for Balinese snacks used in carrying out ceremonies. This is an opportunity for the Balinese snack business to develop. The partner in this community empowerment activity is Jajan Upakara Bali, which is located in Uluwatu Gang Menaga Jati No 8 Jimbaran. Bali Upakara Snacks is a small business that produces snacks for religious ceremonial activities consisting of Balinese uli and begina. Because it is a business derived from tradition, there are several obstacles in the form of limited production aids, product packaging, lack of financial management and limitations in terms of marketing. Based on the problems, phased activities will be carried out starting from production management to marketing. Activities began with providing grating machines, stoves, frying pans, sealer, snack drying mats, iron storage boxes, providing packaging assistance and packaging labels, packaging training, financial management training, making media social media and training. Based on the results of the evaluation, the first stage was obtained by adding production equipment, accelerating the production process by 50% and saving 50% production time. 100% of products contain packaging labels. Keywords: business empowerment; ceremonial facilities; balinese snacks